Asuhan Keperawatan pada Lansia Wanita dengan Penerapan Pelvic Floor Muscle Exercise terhadap Frekuensi Berkemih - Anita Pratamah; Aniska Indah Fari; M.K. Fitriani Fruitasari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
In old age, physiologically the body's cells can decline, resulting in decreased body function and endurance. One example is the urinary system which will affect changes or instability in the function of the urinary tract, so that the elderly will experience abnormal urination patterns. The management that can be carried out as an effort to restore the function of the urinary tract, especially the frequency of urination, is pelvic floor muscle exercise. Can analyze gerontic nursing care in the elderly to control decreased urinary tract function. This case study uses a descriptive method with a nursing process approach which was carried out on 3 patients using a one group pretest posttest research design. There was a change in the frequency of urination in the three respondents who had implemented pelvic floor muscle exercises. It is hoped that this nursing care report can become a reference in gerontic nursing care for the elderly with decreased urinary tract function.